Managing IT in government, business & communities - Gingrich, Gerry; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2003)
"Governments around the world are now placing increasing importance upon the success of small business entrepreneurs and are providing increased resources to support this emphasis. The simple fact that organizations and society are relying heavily on virtual technologies for communication and information management has presented government officials and information resource management practitioners alike with a variety of issues and challenges associated with attempting to managing resources and applications in the world economy. This book presents the most current research and findings about these issues and challenges"--Provided by publisher.
1. Adopting the entrepreneurial process in the study of information systems and small business / M. Hunter, Wayne Long -- 2. Optimal purchase decision criteria for information technology / P. Chong ... [et al.] -- 3. Creating intranets for management and collaboration in federal agencies / Julianne Mahler, Priscilla Regan -- 4. Maintaining the own responsibility / Ruediger Weissbach -- 5. Using spreadsheets as a decision support tool / Stephen Burgess, Don Schauder -- 6. Teaching technology for community / E. Jessup -- 7. Information resources development in China / Lai Maosheng, Fu Xin, Zhang Liyang -- 8. An analysis of factors that influence the ability of SMEs to derive benefit in four phases of electronic commerce / Stephen Chau, Paul Turner -- 9. Electronic government in Japan / Tatsumi Shimada, Kiyoshi Ushida -- 10. Concerns and solutions on electronic voting systems adoption / Yurong Yao, Edward Watson -- 11. SME barriers to electronic commerce adoption / Carina Ihlstrom ... [et al.] -- 12. E-business development issues in UK SMEs / Fiona Meikle, Dianne Willis -- 13. The game of internet B2B / Thomas Daniel, Teoh Yen -- 14. Virtualisations and its role in business / Jerzy Kisielnicki -- 15. Virtual organization / Jinyoul Lee, Bandula Jayatilaka -- 16. Interorganizational relationships, strategic alliances, and networks / Keiichi Yamada -- 17. The internationalization efforts of small internet retailers / Anand Ramchand, Shan-Ling Pan -- 18. Using the web for enhancing decision-making / David King.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 6, 2010).
Keywords: Information resources management; Electronic books